2012
DOI: 10.1016/j.bandl.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of speech fluency in Lewy body spectrum disorder

Abstract: Few studies have examined connected speech in demented and non-demented patients with Parkinson’s disease (PD). We assessed the speech production of 35 patients with Lewy body spectrum disorder (LBSD), including non-demented PD patients, patients with PD dementia (PDD), and patients with dementia with Lewy bodies (DLB), in a semi-structured narrative speech sample in order to characterize impairments of speech fluency and to determine the factors contributing to reduced speech fluency in these patients. Both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 61 publications
(74 reference statements)
10
58
1
Order By: Relevance
“…Similarly, the grammatical expression, characterized by a reduction of well-formed sentences and of dependent clauses, is significantly compromised in persons with PDD and LBD, but not in non-demented PD patients (Ash et al, 2011, 2012b; Ash and Grossman, 2015). Speech rate appears to be useful in distinguishing PDD from LBD, with persons with PDD being less impaired and producing a higher average of words per minute (Ash et al, 2011, 2012b).…”
Section: Results: Relevant Features and Linguistic Profiles Of The Mamentioning
confidence: 99%
“…Similarly, the grammatical expression, characterized by a reduction of well-formed sentences and of dependent clauses, is significantly compromised in persons with PDD and LBD, but not in non-demented PD patients (Ash et al, 2011, 2012b; Ash and Grossman, 2015). Speech rate appears to be useful in distinguishing PDD from LBD, with persons with PDD being less impaired and producing a higher average of words per minute (Ash et al, 2011, 2012b).…”
Section: Results: Relevant Features and Linguistic Profiles Of The Mamentioning
confidence: 99%
“…Decreased speech rate has also been documented in non-aphasic patients with behavioral variant frontotemporal degeneration (Ash et al, 2006) and amyotrophic lateral sclerosis (Ash et al, 2015). We have previously shown that patients with PDSD have reduced speech fluency as well (Ash et al, 2012). In the present study, speech rate was impaired in DEM but not in NON-DEM, and moreover speech rate declined from Time 1 to Time 2 in DEM.…”
Section: Discussionmentioning
confidence: 99%
“…It has become clear in more recent studies that some aspects of language receive bilateral support. For example, speech rate recently has been associated with bilateral frontal regions, particularly in individuals who are aging or have a neurodegenerative disease (Ash et al, 2012; Grossman et al, 2013; van Oers et al, 2010). In the present study, we investigate whether atrophy at baseline in brain regions important for language predicts longitudinal speech production deficits in PDSD.…”
Section: Introductionmentioning
confidence: 99%
“…According to the team, the speech of PD patients is characterized by pauses in sentences now and then. Examining grammatical aspects of language, namely sentence processing in patients with PDD and LB, Grossman et al's (2012) study deonstrated that there is a selectively slow processing of lengthened ambitious sentences in the two subtypes of dementia. Conclusions to be drawn from such studies need much more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Such guidelines, however, encouraged many researchers to investigate the relationship between language and dementia types. Testing the speech in demented and non-demented patients with PD, the study of Ash et al, (2012) concluded that speech fluency is reduced in these patients. According to the team, the speech of PD patients is characterized by pauses in sentences now and then.…”
Section: Introductionmentioning
confidence: 99%